Analyse de la conformité des matières du site Podcast Français Facile avec les plans d’apprentissage semestriels du cours Français Oral Élémentaire - Siti Nurjamilah; Aisyiah Al Adawiyah (Universitas Negeri Semarang, 2024)
This research was conducted to explore the benefits of the Podcast Français Facile site to be used as alternative teaching materials for the Français Oral Élémentaire (FOÉ) course by analyzing the materials that are following the Semester Learning Plan (RPS) of the FOÉ course. The purpose of this study is to explain the results of the analysis of the suitability of the material from the Podcast Français Facile site with FOÉ courses, especially listening skills (Compréhension Orale). This qualitative research uses a qualitative descriptive research approach. The data collection technique used is documentation with all podcast audio on the site Podcast Français Facile as the population and the research samples are débutant-level audio podcasts or DELF A1. The data analysis technique used in this study is a content analysis using data cards. After analysis, the results showed that 17 audio podcasts were following the subject matter of the RPS FOÉ course, those are on Raconter Un Voyage material (3 audio podcasts as appropriate), Faire Des Achats (9 audio podcasts as appropriate), dan Se Faire des Relations (5 audio podcasts as appropriate), so that these materials can be used as alternative teaching materials for FOÉ courses.